Inventarisasi dan Analisis Identifikasi Penggunaan Lahan Berdasarkan Tumpang Tindih Lahan Kontrak Karya pada PT. Gorontalo Mineral - Halid, Amir; Fauzi, Akhmad (Jurnal Agroteknotropika, 2012)
Bone Bolango region located in Gorontalo Province covers an area of 188,006.43 ha which consist of 142,664.38 ha (75,88%) forest and 45,326,5 ha (24,22%) is regional estated. The regency is endowed with rich mineral resources, yet it finds some difficulties in planning and developing ist regional economics, such as how to arrange the regional planning which is based on existing land. The government has already issued licences for optimalyzed the resource for a mining company (kontrak karya). This condition has created un-fair competition between government and society and also society and company which tend to create conflicts over resurces. This case emerged when there was institutional vacuum particularly from forestry Department as the forestry national utirization also the company who has a licency of mining consetion. The Illegal Mining activities, agriculture, garden, and region estated is developing and become informal institutional or shadow economy to fulfil the uncertainty of resources outority from the nation.